1989
DOI: 10.1152/ajpregu.1989.256.4.r822
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing reflex elicited by water and taste solutions in humans

Abstract: We investigated whether water and taste solutions are adequate stimuli for elicitation of the swallowing reflex from the pharyngolaryngeal region in humans. Subjects were five healthy males. Small amounts of water and taste solutions were applied to the posterior tongue of the subject as he reclined on a dental chair. The latency between the onset of application of the stimuli and the occurrence of swallowing was measured. Water was a most effective stimulus for elicitation of the swallowing reflex. The stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 0 publications
3
38
0
Order By: Relevance
“…In addition, in the laryngeal regions, water stimulation is effective in eliciting the swallow reflex. [13][14][15] In experimental animals, electrical stimulation of the peripheral nerves innervating the pharynx and larynx is also used to elicit the swallow reflex. In particular, repetitive electrical stimulation of the SLN can elicit the reflex "like magic."…”
Section: Neural Mechanisms and Effective Sen-sory Inputs For Swallow mentioning
confidence: 99%
“…In addition, in the laryngeal regions, water stimulation is effective in eliciting the swallow reflex. [13][14][15] In experimental animals, electrical stimulation of the peripheral nerves innervating the pharynx and larynx is also used to elicit the swallow reflex. In particular, repetitive electrical stimulation of the SLN can elicit the reflex "like magic."…”
Section: Neural Mechanisms and Effective Sen-sory Inputs For Swallow mentioning
confidence: 99%
“…It has been generally accepted that water is a physiological stimulus (25)(26)(27). Therefore, the results suggest that NO is involved in reflex swallowing from the pharynx under physiological conditions.…”
Section: Discussionmentioning
confidence: 67%
“…Kajii et al (19) reported that sour taste stimulation of the pharynx and larynx facilitated reflex swallowing in rats. Some previous studies have also described that application of water to the pharynx and larynx evokes reflex swallowing in rats (19), rabbits (6) and humans (20). The spatiotemporal summation of primary afferent signals from the GPN-ph and SLN may be the mechanism underlying the enhancement of reflex swallowing by natural stimulation of the pharynx and larynx.…”
Section: Discussionmentioning
confidence: 91%
“…The speed of food bolus movement to the oropharynx and larynx differs depending on the type of food (solid food or liquid). Chemical or mechanical stimulation of the pharyngeal and laryngeal mucosa is thought to be involved in evoking reflex swallowing (6,11,(14)(15)(16)(17)19,20), suggesting that inter-activation of afferent signals from the pharynx and larynx plays a crucial role. However, it is still unknown how these afferent inputs from the oropharynx and larynx interact and how they are involved in evoking reflex swallowing.…”
Section: Originalmentioning
confidence: 99%